2018
DOI: 10.1016/j.microc.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and ion irradiation effects on azurite, malachite and alizarin pictorial models

Abstract: The analysis by intense radiation sources of painting materials used in artworks gives valuable information about their composition and state of conservation, but it can also induce undesired modifications on the studied substrates. Here we use X-ray photoelectron spectroscopy (XPS) to follow the surface chemical changes that prolonged irradiation with soft X-rays (with maximum doses ranging from ~ 1.2x10 17 to ~ 3.4x10 17 photons cm -2 ) produce on azurite, malachite and alizarin pigments and on two egg-yolk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…The O ox /Cu content decreases from 1.9 to 1.2. Such studies have already been realized on copper‐carbonate compounds, 6 pure azurite 2CuCO 3 .Cu(OH) 2 , and malachite CuCO 3 .Cu(OH) 2, for exposure times ranging up to nearly 56 h and a dose of 2.4.10 17 photons cm −2 (Mg anode). Authors have also evidenced a significant Cu(I) peak increase in time, and thus a progressive photoreduction, but over a larger timescale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The O ox /Cu content decreases from 1.9 to 1.2. Such studies have already been realized on copper‐carbonate compounds, 6 pure azurite 2CuCO 3 .Cu(OH) 2 , and malachite CuCO 3 .Cu(OH) 2, for exposure times ranging up to nearly 56 h and a dose of 2.4.10 17 photons cm −2 (Mg anode). Authors have also evidenced a significant Cu(I) peak increase in time, and thus a progressive photoreduction, but over a larger timescale.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5] Despite the high potential of this technique, artifacts associated with X-ray exposure, UHV conditions during analysis, or the use of Ar + sputtering (surface cleaning or depth profiling) have been reported and also closely linked to the nature and hydration level of the compounds, requiring specific attention to avoid misinterpretations. [5][6][7] Irradiation damage induced by X-ray and electron beams has been evidenced, but not clearly explained. Different behavior has been observed depending on the Cu phase and the X-ray source employed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multi-technique approach is also a good practice to ensure the reliability of the chemical information obtained. Different studies have shown for example the instability of copper compounds under X-Ray irradiation [17] and so evidenced the difficulty to implement XPS without modifying the initial information about the oxidation degree. This specific question will be treated in more details in a future paper.…”
Section: Introductionmentioning
confidence: 99%
“…Cardell et al [21], working with azurite rabbit glue-based tempera mock-ups subjected to a UV-aging test, found that the paints made with the finer grained pigments displayed yellowing, which was related to modifications of the binder structure. Other works also proved that X-rays were able to deteriorate the lipids and proteins of egg yolk present in tempera mock-ups made with either azurite, malachite, or alizarin, affecting the cleavage of the C-N, C-O(H), and C=O bonds [59]. In our work, despite the fact that R-based paints exhibit a hydrophobic character, the binder loss in these paints was more significant than in the E-based paints.…”
mentioning
confidence: 97%